THE METHOD OF ANALYSIS OF HIERARCHIES IN THE SYSTEM OF COMPLEX PROTECTION OF INFORMATION OBJECTS - Irina Sergeevna Klimenko (Современная наука и инновации)
The solution of the problem of ensuring information security of subjects and objects of information relations implies the existence of a system of flexible and prompt response to threats and attacks. The main purpose of the article is to justify the expediency of applying the method of analyzing hierarchies to algorithms for complex protection of information objects.